1996
DOI: 10.1002/vnl.10092
|View full text |Cite
|
Sign up to set email alerts
|

An example of rigid PVC foam formulating using a statistical experimental design approach

Abstract: A study was undertaken to understand the effect of PVC molecular weight, modifier molecular weight, and modifier loading on die swell and foam density in a rigid PVC formulation. We used a statistical experimental design to separate the effects from the noise of normal experimentation. Die swell and foam density of extruded pieces were measured and analyzed in a commercially available software package. Analysis of the experimental data shows that the die swell response is linear over the experimental range, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…19 Two chemical blowing agents are frequently used in PVC foaming: azodicarbonamide (exothermic blowing agent), which gives relatively fast foaming at a more narrow temperature range (175 to 233 o C), and sodium bicarbonate (the endothermic blowing agent), which gives longer foaming times and has a broader range of decomposition temperature (143 to 240 o C). 82,84 Foam density is not only important because of the weight of material and cost but it also affects many mechanical parameters such as tensile strength, tensile modulus, flexural strength, impact strength, and deflection temperature, all of which decrease with density decreasing. 79 If too high a quantity of blowing agent is added, cells collapse, producing denser foam.…”
Section: Process Aidsmentioning
confidence: 99%
“…19 Two chemical blowing agents are frequently used in PVC foaming: azodicarbonamide (exothermic blowing agent), which gives relatively fast foaming at a more narrow temperature range (175 to 233 o C), and sodium bicarbonate (the endothermic blowing agent), which gives longer foaming times and has a broader range of decomposition temperature (143 to 240 o C). 82,84 Foam density is not only important because of the weight of material and cost but it also affects many mechanical parameters such as tensile strength, tensile modulus, flexural strength, impact strength, and deflection temperature, all of which decrease with density decreasing. 79 If too high a quantity of blowing agent is added, cells collapse, producing denser foam.…”
Section: Process Aidsmentioning
confidence: 99%
“…Poly(vinyl chloride) (PVC) is one of the most widely used thermoplastics today and PVC compounds, formulated with various additives, are versatile plastics with numerous applications in a variety of industries. PVC‐based foamed products can be produced by melt extrusion with the inclusion of a chemical blowing agent, which produces a gas such as nitrogen or carbon dioxide .…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the results published, it can be concluded that factors such as PVC grade , additive type and content , and the type of NC , together with the preparation methods, strongly influence either the structure or the properties of prepared PVC/NC nanocomposites. They should therefore be well‐identified in order to control the properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation